2022
DOI: 10.3847/2041-8213/ac86d4
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Premerger Shock in an Intercluster Filament in Abell 98

Abstract: We report the first unambiguous detection of an axial merger shock in the early-stage merging cluster Abell 98 using deep (227 ks) Chandra observations. The shock is about 420 kpc south from the northern subcluster of Abell 98, in between the northern and central subclusters, with a Mach number of  ≈ 2.3 ± 0.3. Our discovery of the axial merger shock front unveils a critical ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 43 publications
(79 reference statements)
4
13
0
Order By: Relevance
“…This study also determined that A98S has an asymmetric ICM distribution, indicating that A98S is still undergoing a major merger. Sarkar et al (2022) found definitive evidence of a shocked edge to the south of A98N with deeper Chandra observations, confirming that A98N and A98S are likely in the early stages of a merging event.…”
Section: Introductionsupporting
confidence: 59%
“…This study also determined that A98S has an asymmetric ICM distribution, indicating that A98S is still undergoing a major merger. Sarkar et al (2022) found definitive evidence of a shocked edge to the south of A98N with deeper Chandra observations, confirming that A98N and A98S are likely in the early stages of a merging event.…”
Section: Introductionsupporting
confidence: 59%
“…Figure 1 shows a slightly smoothed image of A98N (northern sub-cluster) and A98S (central sub-cluster) in the 0.5-2 keV band, obtained after co-adding all ten observations and by applying the correction for exposure non-uniformity. As reported by earlier studies, the cluster is an early-stage merger, with the merger axis likely aligned along a local N-S large-scale filament connecting A98N and A98S (e.g., Paterno-Mahler et al 2014;Alvarez et al 2022;Sarkar et al 2022).…”
Section: Imaging Analysismentioning
confidence: 64%
“…α 1 and α 2 are the slopes inside and outside the edge, respectively. We project the estimated emission measure profile onto the sky plane and fit the observed surface brightness profile by varying the slopes, edge radius, and the magnitude of the jump (similar to what we did for the shock front in paper I; Sarkar et al 2022). Figure 3 displays the bestfit models (red) and the 3D density profiles (inset) for both directions.…”
Section: A98nmentioning
confidence: 97%
See 2 more Smart Citations